Borcherds products on unitary groups - Hofmann, Eric (Mathematische Annalen, 2014)
In the present paper, we provide a construction of the multiplicative Borcherds lift for unitary groups \mathrm U (1,m), which takes weakly holomorphic elliptic modular forms as input functions and lifts them to automorphic forms having infinite product expansions and taking their zeros and poles along Heegner divisors.